Evaluation of the Impact of Meningococcal Serogroup A Conjugate Vaccine Introduction on Second-Year-of-Life Vaccination Coverage in Burkina Faso. (31st October 2019) - Zoma, Robert L; Walldorf, Jenny A; Tarbangdo, Felix; Patel, Jaymin C; Diallo, Alpha Oumar; Nkwenkeu, Sylvain F; Kambou, Ludovic; Nikiema, Moumouni; Ouedraogo, Arnaud; Bationo, Ange B; Ouili, Romeo; Badolo, Hermann; et al.
Abstract: Background: After successful meningococcal serogroup A conjugate vaccine (MACV) campaigns since 2010, Burkina Faso introduced MACV in March 2017 into the routine Expanded Programme for Immunization schedule at age 15–18 months, concomitantly with second-dose measles-containing vaccine (MCV2). We examined MCV2 coverage in pre- and post-MACV introduction cohorts to describe observed changes regionally and nationally. Methods: A nationwide household cluster survey of children 18–41 months of age was conducted 1 year after MACV introduction. Coverage was assessed by verification of vaccination cards or recall. Two age groups were included to compare MCV2 coverage pre-MACV introduction (30–41 months) versus post-MACV introduction (18–26 months). Results: In total, 15 925 households were surveyed; 7796 children were enrolled, including 3684 30–41 months of age and 3091 18–26 months of age. Vaccination documentation was observed for 86% of children. The MACV routine coverage was 58% (95% confidence interval [CI], 56%–61%) with variation by region (41%–76%). The MCV2 coverage was 62% (95% CI, 59%–65%) pre-MACV introduction and 67% (95% CI, 64%–69%) post-MACV introduction, an increase of 4.5% (95% CI, 1.3%–7.7%). Among children who received routine MACV and MCV2, 93% (95% CI, 91%–94%) received both at the same visit. Lack of caregiver awareness about the 15- to 18-month visit and vaccine unavailability were common reported barriers to vaccination. Conclusions: A small yet significant increase in national MCV2 coverage was observed 1 year post-MACV introduction. The MACV/MCV2 coadministration was common. Findings will help inform strategies to strengthen second-year-of-life immunization coverage, including to address the communication and vaccine availability barriers identified.